Prevalence and associated factors to the cosmetic doping among fitness-centers customers - Lima-Oliveira, Jhonatan; Schwingel, Paulo Adriano (ABCS Health Sciences, 2015)
Introduction: The rise in the cult of the body in modern society has led many fitness-centers customers to the systematic practice of intramuscular oil injections, procedure called cosmetic doping. Therefore, this study aimed to determine the prevalence of cosmetic doping in the São Francisco Valley region, in order to establish the sociodemographic and clinical profiles of this group of individuals. Case report: This is a retrospective documentary study with analysis of 346 records from fitness-centers customers, of which 7 reported use of cosmetic doping. Sociodemographic, kinanthropometric, hemodynamic, personal and family past medical history and the consumption of licit and illicit drug data were collected from these records. The prevalence of cosmetic doping was 2.0% (95%CI 0.8–4.1), and most of the users are young adults with high school graduates, middle-class workers, and are considered physically active with low body fat mass. They use concomitantly dietary supplements, anabolic steroids and other illicit drug. Conclusions: The findings of the study contribute in determining the profile of this population, demonstrating that users of cosmetic doping are young adults concerned with aesthetic body. The sociodemographic characteristics found in this study differ from previous studies in the level of education, income and occupation. In this sense, actions to raise awareness of this population about the risks and dangers of the cosmetic doping should be supported as soon as possible.